The role of differentiated learning rooted in local wisdom in the development of civic literacy of elementary school students - Sinahika Sajar; Maretha Dellarosa; Ganesh Gunansyah (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2026)
Citizenship literacy is a fundamental competency that must be developed from basic education to form critical, participatory, and responsible citizens. This study aims to examine the role of differentiated learning based on local wisdom in developing the civic literacy of elementary school students through a systematic review of empirical and conceptual evidence. The research method uses a systematic review approach of 20 research articles published in the 2021-2025 period, focusing on the Indonesian and international education context. The analysis was carried out on three main aspects: differentiated learning strategies based on local wisdom, the effectiveness of the culturally responsive approach, and its impact on students' civic literacy. The results showed that differentiated learning that integrated local wisdom significantly improved students' understanding of citizenship, social participation, and active engagement. Learning models based on local wisdom projects, innovative tradition-based media, and contextual gamification have proven to be effective in improving cultural and civic literacy. The Culturally Responsive Teaching approach increases civic knowledge scores, engagement, and willingness to discuss civic issues. The findings also identified implementation challenges including limited teacher training, rigid curriculum, and limited resources. This research recommends curriculum reform, teacher capacity building through systematic training, integration of learning technologies, and strengthening school-community synergy to optimize the development of local wisdom-based civic literacy in primary schools